Production of TNF-α in macrophages activated by T cells, compared with lipopolysaccharide, uses distinct IL-10-dependent regulatory mechanism. - Agbanoma, G; Li, C; Ennis, D; Palfreeman, A; Williams, L; Brennan, F (2012)
Previously, we demonstrated that spontaneous TNF-α production by macrophages in rheumatoid arthritis (RA) synovial tissue is largely driven by contact-dependent activation with T cells in that tissue. Whereas abundant IL-10 is present in these RA synovial cultures, it does not adequately control the production of TNF-α. In this study, we have compared the mechanisms involved in IL-10-mediated TNF-α regulation in LPS-stimulated macrophages with macrophages stimulated with activated T cells. We confirm that in LPS-stimulated macrophages the 3' enhancer region of tnf is essential for tnf transcription, and its regulation by IL-10 is dominated by a STAT3-dependent pathway. However, in contrast, we have found that tnf transcription in macrophages stimulated by activated T cells or by RA synovial T cells does not require the 3' enhancer region of tnf, and that its regulation by IL-10 is subsequently altered and clearly is not mediated by a dominant STAT3 pathway. These observations have very important implications for our understanding as to how IL-10 regulates TNF-α production at sites of chronic inflammation, such as the synovial tissue of patients with RA. Furthermore, these distinct IL-10 mechanisms will have bearing upon the identification of potential therapeutic targets in RA synovial macrophages where the activation stimulus is clearly not LPS.